Using New Technologies for Teaching and Learning Science - Guillermina Waldegg Casanova (Universidad Autónoma de Baja California, 2002)
Given the irreversible presence of the new information and communication technologies (ICTs) in everyday life, particularly the Internet, it is necessary to clarify the different roles and uses they can have in education, and to review and assess the main trends in their scholastic application. Recent educational research on the use of ICTs has developed a series of new concepts and new approaches that have caused a notable evolution of the field of teaching and learning. These approaches all have in common the fact that they belong to currents of socio-constructivist thought. The papers show that ICTs can implement pedagogical principles in which the student is the main actor in constructing his/her own knowledge, and s/he can learn better in the context of a concrete and meaningful, and at the same time, collective action.